Genomes and virulence difference between two physiological races of Phytophthora nicotianae - Liu, Hui (Gigascience, 2016)
BACKGROUND: Black shank is a severe plant disease caused by the soil-borne pathogen Phytophthora nicotianae. Two physiological races of P. nicotianae, races 0 and 1, are predominantly observed in cultivated tobacco fields around the world. Race 0 has been reported to be more aggressive, having a shorter incubation period, and causing worse root rot symptoms, while race 1 causes more severe necrosis. The molecular mechanisms underlying the difference in virulence between race 0 and 1 remain elusive. FINDINGS: We assembled and annotated the genomes of P. nicotianae races 0 and 1, which were obtained by a combination of PacBio single-molecular real-time sequencing and second-generation sequencing (both HiSeq and MiSeq platforms). Gene family analysis revealed a highly expanded ATP-binding cassette transporter gene family in P. nicotianae. Specifically, more RxLR effector genes were found in the genome of race 0 than in that of race 1. In addition, RxLR effector genes were found to be mainly distributed in gene-sparse, repeat-rich regions of the P. nicotianae genome. CONCLUSIONS: These results provide not only high quality reference genomes of P. nicotianae, but also insights into the infection mechanisms of P. nicotianae and its co-evolution with the host plant. They also reveal insights into the difference in virulence between the two physiological races. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13742-016-0108-7) contains supplementary material, which is available to authorized users.